(untitled) (Biological Sciences - PJSIR, 1999)
belonging to Apocynaecea and Zygophyllaecea families respectively (Hooker 1882) which are grown all over pakistan and have anticancer property (Watt 1890; Chakraborti and Mukherji 1968; Siddiqui and Bukhari 1972).